On Meat, Butter, and Fudge. (2nd January 2020) - Potter, John D.; Jackson, Rod
Abstract: Was the Annals of Internal Medicine recently acting as a mouthpiece for meat-industry propaganda? Five papers underpinned recommendations on meat consumption; their central deceit was to review only randomized controlled trials and cohort studies, which, in research on the associations between common foods and disease outcomes, are nearer to the bottom than the top of the evidence hierarchy. Despite concluding that their own recommendations were "weak and based on low certainty evidence", the authors were happy to recommend that there is "No need to reduce red or processed meat consumption for good health." What we actually know is that: red meat consumption is an order of magnitude higher now than through most of human history; red meat is a probable, and processed meat is a definite, human carcinogen; saturated fat increases risk of heart disease; and vegans and vegetarians have better lipid profiles, lower risk of chronic disease, and greater longevity than meat eaters. There are other consequences of meat consumption too, including: altered sexual development; widespread antimicrobial resistance; and disrupted planetary health, including depletion of aquifers, groundwater pollution, and increased greenhouse gases. The pseudoscience presented in the Annals of Internal Medicine appears to have been written solely to create doubt and confusion in the wider population. Scientists and journals should hold themselves to a higher standard.